2016
DOI: 10.1073/pnas.1613406113
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis at the nanoscale may change selectivity

Abstract: Among the many virtues ascribed to catalytic nanoparticles, the prospect that the passage from the macro-to the nanoscale may change product selectivity attracts increasing attention. To date, why such effects may exist lacks explanation. Guided by recent experimental reports, we propose that the effects may result from the coupling between the chemical steps in which the reactant, intermediates, and products are involved and transport of these species toward the catalytic surface. Considering as a thought exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Innovative experimental approaches have shown that the catalytic nature of metals and their oxides is strongly dependent on size, shape and composition 40 . In fact, catalytic selectivity at the nanoscale is drastically altered 41 . Oriented assembly occurs by spontaneous particle fusion along a common growth axis and rotation at interfacial boundaries 42 .…”
Section: Configuring Functional Biomimicry At the Tio2 Surface: Supramentioning
confidence: 99%
“…Innovative experimental approaches have shown that the catalytic nature of metals and their oxides is strongly dependent on size, shape and composition 40 . In fact, catalytic selectivity at the nanoscale is drastically altered 41 . Oriented assembly occurs by spontaneous particle fusion along a common growth axis and rotation at interfacial boundaries 42 .…”
Section: Configuring Functional Biomimicry At the Tio2 Surface: Supramentioning
confidence: 99%
“…Provided that D A = D B , the concentration of B in the above equations can be replaced by c A * − c A , where c A * is the bulk concentration of A. By solving the partial differential equations (7) and (8), the concentrations of A and R can be derived. Therefore, the current can be calculated by:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…At the same time it is important to appreciate that particle size and coverage can profoundly influence the rates of mass transport of reactants and products to and from the active surface. [8][9] This is especially important in the area of multi-electron process where one or more solution phase intermediates are formed, as in the sequential reduction of oxygen via hydrogen peroxide to form water. 10 Then in the simplest case of a so-called ECE process (in the Testa and Reinmuth notation E corresponds to an electron transfer and C to a chemical step): (1)…”
Section: Introductionmentioning
confidence: 99%
“…Under real extreme or harsh conditions such as high temperature, the detailed evolution of Ni–Au dumbbell structure and its underlying atomistic processes deserve to be studied in depth. Phase and morphology changes of catalysts have a direct impact on catalytic efficiency and are critical for understanding catalyst failure . In order to understand the behavior of bimetallic catalysts, we perform an in situ experiment of Ni–Au dumbbell samples in a scanning transmission electron microscope (STEM) under two different environments.…”
mentioning
confidence: 99%
“…Phase and morphology changes of catalysts have a direct impact on catalytic efficiency and are critical for understanding catalyst failure. [10] In order to understand the behavior of bimetallic catalysts, we perform an in situ experiment of Ni-Au dumbbell samples in a scanning transmission electron microscope (STEM) under two different environments. We heat up the catalyst to 700 °C under high vacuum, and directly Conversion of CO 2 gas to CO fuels is one of the most promising solutions for the increasing threat of global warming and energy crisis.…”
mentioning
confidence: 99%